Choice of Law dan Choice of Forum dalam Sengketa Ekonomi Syariah: Implikasi bagi Penyelesaian Sengketa Bisnis Syariah di Indonesia - Amran Al Farisy; Muhammad Alfathan Herdy; Faisal Nasrullah (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2024)
This study examines the application of the Choice of Law and Choice of Forum principles in sharia economic disputes in Indonesia, which involve interactions between religious and national legal systems. The main issue discussed is how these two principles affect the efficiency and legal certainty in resolving sharia business disputes. The purpose of this study is to analyze the legal dynamics that occur between the Religious Court and the National Sharia Arbitration Board (BASYARNAS), and its implications for resolving sharia business disputes in Indonesia. This study uses a normative research method with a document analysis and case study approach. The main results achieved show that the application of the Choice of Law and Choice of Forum principles in Indonesia still faces challenges in the form of unclear legal authority between the Religious Court and BASYARNAS, as well as legal uncertainty that hinders the efficiency of dispute resolution. However, the application of an appropriate sharia dispute resolution mechanism can increase legal certainty, efficiency, and reduce costs in the sharia business dispute process. The conclusion of this study is that the application of the principles of Choice of Law and Choice of Forum that are harmonious and clear is very important to ensure fair, fast, and efficient dispute resolution, and support the development of a sustainable sharia economy in Indonesia.